2021
DOI: 10.1186/s12879-021-06663-x
|View full text |Cite
|
Sign up to set email alerts
|

What about the others: differential diagnosis of COVID-19 in a German emergency department

Abstract: Background The ongoing COVID-19 pandemic remains a major challenge for worldwide health care systems and in particular emergency medicine. An early and safe triage in the emergency department (ED) is especially crucial for proper therapy. Clinical symptoms of COVID-19 comprise those of many common diseases; thus, differential diagnosis remains challenging. Method We performed a retrospective study of 314 ED patients presenting with conceivable COVI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Acute syndromes that can mimic MIS-C include Kawasaki disease 3 , toxic shock syndrome 3 , bacterial or viral sepsis 4 , and even non-infectious conditions such as congestive heart failure, whether or not directly related to MIS-C 16 . In contrast, acute illnesses that can mimic severe COVID-19 include many infections [17][18][19] , including those caused by respiratory viruses (e.g., influenza virus, parainfluenza virus, adenovirus, etc. ), bacterial pneumonia, including tuberculosis, malaria, and chronic obstructive pulmonary disease exacerbation.…”
Section: Resultsmentioning
confidence: 99%
“…Acute syndromes that can mimic MIS-C include Kawasaki disease 3 , toxic shock syndrome 3 , bacterial or viral sepsis 4 , and even non-infectious conditions such as congestive heart failure, whether or not directly related to MIS-C 16 . In contrast, acute illnesses that can mimic severe COVID-19 include many infections [17][18][19] , including those caused by respiratory viruses (e.g., influenza virus, parainfluenza virus, adenovirus, etc. ), bacterial pneumonia, including tuberculosis, malaria, and chronic obstructive pulmonary disease exacerbation.…”
Section: Resultsmentioning
confidence: 99%
“…Triage is an effective process for ensuring that effective emergency care is provided despite limited resources by sorting and prioritizing patients to appropriate orders for visits based on their urgency degree. Risk stratification is one of the central challenges of emergency medicine ( 5 7 ). Due to non-eye practitioners’ limited knowledge and training in ophthalmology, the problem of identifying vision-threatening patients is highlighted in ophthalmic emergencies ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to non-eye practitioners' limited knowledge and training in ophthalmology, the problem of identifying visionthreatening patients is highlighted in ophthalmic emergencies (8, 9). Historically, registered nurses have been the first line to perform triage in many countries' EDs (6). Previous studies have found that nurses in general EDs tend to assign patients to more urgent categories to avoid missing critical patients (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue is a common symptom in those with symptomatic COVID-19 and also persists after COVID-19 32 . Perhaps the fact that both respiratory distress and fatigue are associated not only with Sars-Cov-2 but also with other diseases, like, cardiopulmonary, renal, gastrointestinal, oncology, and infectious diseases 33 – 36 , may explain why these symptoms are not associated solely with positive cases of Sars-Cov-2.…”
Section: Discussionmentioning
confidence: 99%